The Use of Anecdote Stories to Enrich EFL College Students' Vocabularies and to Reduce Their Reading Anxiety - Elya Haviza; Leni Marlina (Universitas Negeri Padang, 2022)
This study uses quasi-experimental methods. The aim of this research is to investigate the effect of Anecdote Stories To Enrich EFL College Students’ Vocabularies and To Reduce Their Reading Anxiety At English Department. The population of this research were EFL Students’ At English Department UNP. The research sample was 45 students which were divided into two classes which are 25 students from class K’2 and 20 students from NK’1. This study's instrumentation consisted of a pre-test and post-test vocabulary test with 100 short answer questions, as well as a reading anxiety test. The results of those tests were obtained after analyzing the data with SPSS 26 for Windows' Paired sample T-test. It shows the mean of pre-test and post-test score in K’2 classes were 51,20 and 56,00. Meanwhile the mean of pre-test and post-test score in the NK'1 classes were 47,90 and 52,90. Moreover, pupils’ result for students anxiety after conducted reading anxiety test in form of pre-test and post-test indicated that are 4% rising score in agree point while pre-test was 41% and post-test was 45% in K2 classes. In NK2 classes, the differences can be seen in strongly agree point, with 4% rising score from 5% strongly agree to 9% strongly agree. Based on the findings, it can be concluded that students who learn through anecdotes as teaching medium do better than students who learn through conventional media. Moreover, reading anxiety of the students decrease because a lot of them have self-confident to answer the post-test in reading anxiety test after conducted the anecdote. The level's significance is 0.05, which is higher than the significance test, which is 0.000 with a degree of 5 percent. Moreover, it is also found that the anecdotes can reduce EFL students’ reading anxiety at Universitas Negeri Padang especially in English major classes.